Shelf life study of quick cooking rice (PSCBRc 18) using laminated nylon polyethelene bags - Ortega, Melba P.
This study aims essentially to upscale of quick-cooking rice from laboratory scale to bench scale and to conduct shelf life study of QCR using Philippine rice cultivar PSBRc 18. Phase I dealt with the step-wise upscaling of the process for QCR from 25 to 1000 g. The general procedure for QCR produuction were hydration, gelatinization and rehydration. This process was developed by the UP CHE-PhilRice Research Project entitled "Rice and Rice-based Disaster Foods" (Azanza et al., 1998). The hydration step involved soaking the rice in a mixture of 0.5% solution of calcium chloride and 0.5% sodium citrate using 1:2 rice to mixture ratio maintained at 50°C for 15 min. Gelatinization times for 100, 500, and 1000 g rice were determined using steam under pressure at 15 psi (121.5°C). Results showed that the minimum times to attain at least 90% gelatinization for 100, 500, and 1000 g test weights were 4, 6, and 10 min, respectively. The drying times for 100, 500, 1000 g gelatinized rice were determined using a convective air-drier equipped with fan and heater. A ten-fold in weight resulted to a corresponding 18% increase in the length of drying time. Optimum rehydration times for 5, 25, 50, and 100 g of dried rice were determined by boiling QCR in water using 1:3 QCR to water ration. Water uptake ratio, percent clumpiness, and percent breakage were used parameters for characterization of rehydrated QCR. An optimum range of rehydration time for 5 to 100 g QCR was found to be between 5-9 min. Moisture sorption isotherm properties of QCC, established using the Wink's equilibrium method, yielded a sigmoidal curve by plotting the %EMC against aw values which ranged from 0.10 to 1.0. Monolayer value of 6.56% was calculated using the BET equation. Graphical analysis of Henderson's equation yielded the Zone II boundaries at 6.00% and 18.29% at corresponding aw level of 0.20 and 0.75, respectively. Within this region, maximum shelf stability of QCR is expected. The shelf-life of QCR packed in laminated nylon polyethylene at normal conditions of 28°C and 75% RH was computed at 219 days using the HVP method. Microbial, physico-chemical, and sensory assessments of stored QCR were monitored at various aw. Freshly processed samples had the following characteristics: 6.72% moisture content; 0.525 aw; 1.9 x 10^2 cfu/g TPC; <cfu/g YMC of volume expansion ratio of 1.5; water uptake ratio of 3:11; percent clumpiness of 93.60; and 3.80% broken kernels. The freshly prepared QCR was described by panel as near to white in color, slightly glossy, soft, slightly pasty, and has a strong aroma and flavor. Overall, appearance, flavor, and texture acceptability parameters were given ratings of like moderately. At computed shelf life, the QCR with aw of 0.0788 had the following characteristics: moisture content of 14.43%, 0.73; TPC of 1.7 x 10^4 cfu/g; YMC of 8.2 x 10^ cfu/g; 1.52 volume expansion ratio; 2.88 water uptake ratio; 94.50% clumpiness; and 14.0% broken kernels.